(untitled) (Orfeu, 2022)
This is a translation of the interview that Lucy Green gave to Flávia Narita at the Institute of Education in 2011. At that time both Flávia and I were PhD students in London. The choice of translating this interview is due to the fact that it brings the principles of informal music learning. We can see the then a PhD student interviewing her supervisor on the topic of her supervisor’s expertise. After 10 years that this interview has been available on YouTube, I see that its content is still extremely topical and relevant. The original interview lasts 12 minutes and 33 seconds and it has already reached over 18,000 views on the UCL Institute of Education - University College London’s YouTube channel. I hope that the translation of this interview will contribute to the journey of learning and teaching practices of many music students.